1430. Evolving Impact of 13-Valent Pneumococcal Conjugate Vaccine on Invasive Pneumococcal Disease. (26th November 2018) - Yildirim, Inci; Little, Brent A; Shea, Kimberly M; Pelton, Stephen I
Abstract: Background: The 13-valent pneumococcal conjugate vaccine (PCV13) replaced PCV7 in the childhood immunization schedule in Massachusetts (MA) beginning in April, 2010. We describe the current epidemiology of invasive pneumococcal disease (IPD) in Massachusetts (MA) children after introduction of PCV13. Methods: Cases of invasive pneumococcal disease (IPD) in children < 18 years of age were detected through an enhanced surveillance system in MA since 2001. All cases in children and Streptococcus pneumoniae (SP) isolates, when available, are submitted to Department of Public Health (MDPH) and parents/physicians are interviewed for confirmation of demographic and clinical data. All available isolates are confirmed as SP, serotyped by Quellung reaction. Results: There were 351 IPD cases in MA children from April 1, 2010 to September 31, 2017, and 36 (10.3%) were in infants < 6 months; 42 (12.0%) in children between 6 and 12 months; 63 (18.0%) in toddlers 12–24 months; 102 (29.1%) in children aged 2–5 years, and 108 (30.8%) were in children aged ≥5 years. Incidence of IPD declined to 6.8/10 5 children (95% CI 2.6–11.1) in 2015/2016 period which represents a 72.1% decline compared with 2010/2011 (24.4/10 5, 95% CI 16.3–32.5) (figure). However, in 2016/2017, IPD incidence increased to 10.4/10 5 children (95% CI 5.2–15.7). The most common clinical presentation was bacteremia (62.9%), followed by pneumonia (30.5%) and CNS disease (6.6%). Among, 103 (32.6%) children with ≥1 comorbidity, asthma (13.2%), hematologic malignancy (12.1%), prematurity (9.9%) and sickle cell disease (9.9%) were the most common comorbidities. He overall mortality rate was 5.1%. Isolates from 308 (89.3%) were available for serotyping; vaccine serotypes (VST) were identified in 106 (33.3%) IPD cases [19A (46.2%), 7F (19.9%), 3 (17.9%), 19F (10.4%), 6A (2.8%), 14, 18C, 5 (0.9% each). Serotypes 15BC (13.7%), 22F (12.6%) and 33F (11.8%) were the most common nonvaccine serotypes (NVST). Conclusion: Invasive pneumococcal disease identified in the post-PCV13-era is primarily caused by NVSTs, specifically serotypes 15BC, 33F and 22F; and disproportionately observed in children with comorbid conditions. Continued surveillance is necessary to determine the impact of PCV13, as well as track potential changes in disease incidence and character due to NVST. Disclosures: All authors: No reported disclosures.